Reoperation Rates of Percutaneous and Paddle Leads in Spinal Cord Stimulator Systems: A Single-Center Retrospective Analysis - Antonovich, Devin D; Gama, Willy; Ritter, Alexandra; Wolf, Bethany Jacobs; Nobles, Ryan H; Selassie, Meron A; Hillegass, M Gabriel (Pain medicine (Malden, Mass.), 2021)
Abstract Objective We hypothesize that reoperation rates of spinal cord stimulation (SCS) systems utilizing percutaneous leads are comparable to those utilizing paddle leads. We attempt here to characterize causes for those reoperations and identify any related patient characteristics. Design and Subjects This study is a single-center retrospective chart review of 291 subjects (410 operations) who underwent at least one permanent SCS implantation utilizing percutaneous or paddle leads over a 10-year period at the Medical University of South Carolina. Methods Charts were reviewed for height, weight, body mass index, gender, race, age, stimulator type, type of reoperation, diabetes status, history and type of prior back surgery, top lead location, and number of leads placed. Comparisons of patient and procedural characteristics were conducted using a two-sample t test (continuous variables), chi-square, or Fisher exact approach (categorical variables). Univariate and multivariate Cox regression models were developed, identifying associations between patient characteristics, SCS characteristics, reoperation rates, and time to reoperation. Results Thirty point five eight percent of subjects (89/291), required at least one reoperation. The reoperation rate was 27.84% for percutaneous systems (N = 54/194) and 27.78% for paddle systems (N = 60/216). Time to reoperation also did not differ between the two systems (hazard ratio [HR] = 1.06, 95% CI = 0.70–1.60). Of all factors examined, younger age at time of placement was the only factor associated with risk of reoperation (HR = 0.73, 95% CI = 0.62–0.87, P < 0.001). Conclusions Our data suggest that reoperation rates and time to reoperation between percutaneous and paddle leads are clinically similar; therefore, rates of reoperation should have no bearing on which system to choose.